Omega-3 Fatty Acids: Dietary Components for the Promotion of Human and Animal Health - Echeverria-Morgado, J (Polish Acad Sciences, Inst Genetics & Animal Biotechnology, 2025)
Omega-3 fatty acids, commonly found in fish and other natural sources, are essential polyunsaturated fats with significant health benefits. This study provides an overall quantitative literature analysis on omega-3 fatty acids. Bibliometric data were collected through the search string TOPIC = ("omega-3 fatty acid*" OR "omega-3 polyunsaturated fatty acid*" OR "omega-3 fatty acid*" OR "omega-3 polyunsaturated fatty acid*" OR "n-3 fatty acid*" OR "n-3 polyunsaturated fatty acid*" OR "omega-3 oil*"). It yielded 35,575 publications indexed in the online Web of Science Core Collection database. Using VOSviewer software, term maps were generated to visualize frequently mentioned terms together with their citation data. The literature had a steady growth since the 2000s and predominantly consists of original articles, with a ratio of 5.4:1 compared to reviews. The most productive author was Professor Philip C. Calder from University of Southampton, whereas the most productive country was the United States. Fish is a common source of omega-3 fatty acids mentioned by the literature, along with olive oil, corn oil, soybean oil, flaxseed, microalgae, linseed oil, vegetable oil, and seafood. Recurring medical conditions mentioned by the literature included inflammation, cardiovascular disease, cancer, obesity, depression, and diabetes. This bibliometric review highlights the dominant contributors, major research themes, and emerging applications of omega-3 fatty acids in human and animal health.